BF3·OEt2-Catalyzed Rearrangement of Epoxy-Himachalenes: Access to New Biosourced N-Acetamide-Based Himachalenes - Ait El Had, Mustapha; Zaki, Mohamed; Taourirte, Moha; Benharref, Ahmed; Urrutigoïty, Martine; Oukhrib, Abdelouahd (Synlett, 2020)
Biosourced N-acetamide-based himachalenes were synthesized by Lewis acid catalyzed rearrangement of epoxy-himachalene derived from α-cis- and β-himachalenes, the main component of essential oil of Atlas cedar (Cedrus atlantica). Several new chiral polycyclic N-acetamide compounds were obtained with different selectivities depending on the acid used. Among the Lewis acids used, BF3·OEt2 under catalytic and mild conditions is efficient and selective affording the formation of chiral N-acetamides in good yields. Otherwise, using acetonitrile as solvent and reagent was proved as an efficient tool giving access to new N-acetamide-based himachalenes. A mechanism to explain the formation of the different compounds observed in the reaction mixture has also been proposed.
Keywords: sesquiterpene; N-acetamides; Atlas cedar; himachalene; Lewis acids